Analysis of the labor insertion of graduates from FACENA Engineering programs within the framework of CyMAT - Sanabria, Norberto A.; Amarilla, Alicia I.; Peris, José C.; Valdéz, Juan Nápoles (Extensionismo, Innovación y Transferencia Tecnológica, 2020)
This work is carried out within the framework of the research project "Working Conditions and Environment of Students from the Professional Training Course and Graduates of the Current Program of the Engineering Courses of the School of Exact and Natural Sciences and Surveying of the National University of the Northeast (FACENA- UNNE)”. Among the objectives outlined, we seek to investigate the working conditions and environment (CyMAT, Spanish acronym) of the students of the last five years of the FACENA engineering programs, exploring the job profile required by companies and organizations in the field, considering the socioeconomic context of the Northeast region of Argentina (NEA, Spanish acronym). For the development of this work, the labor insertion of graduates from the Electrical Engineering and Electronic Engineering programs is analyzed, taking into account the socioeconomic and demographic situation in the region. It should be noted that the School where students graduate is located in the city of Corrientes, Argentina.